2015
DOI: 10.1007/s00404-015-3840-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of adnexal torsion in premenarchal patients

Abstract: Adnexal torsion in premenarchal patients is rare, presents similarly to older patients, but involves a normal adnexa in 69% of cases, therefore requiring a high index of suspicion in any premenarchal patient with acute onset abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…It has been reported that most of the premenarchal ovarian torsion cases present with abdominal pain and vomiting similar to this case 10. In a study that analysed 16 cases of premenarchal ovarian torsion cases, it has been found that most of the cases had normal-size ovary (69.9%) 10. This is in contrary to our case where the ovary was enlarged in the absence of any cysts which could be due to the compensated hypertrophy.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It has been reported that most of the premenarchal ovarian torsion cases present with abdominal pain and vomiting similar to this case 10. In a study that analysed 16 cases of premenarchal ovarian torsion cases, it has been found that most of the cases had normal-size ovary (69.9%) 10. This is in contrary to our case where the ovary was enlarged in the absence of any cysts which could be due to the compensated hypertrophy.…”
Section: Discussioncontrasting
confidence: 69%
“…Paediatric ovarian torsion is a rare entity, and the estimated prevalence between 1–20 years of age is 0.005% compared with 2.5%–7.5% in the adult population 9. It has been reported that most of the premenarchal ovarian torsion cases present with abdominal pain and vomiting similar to this case 10. In a study that analysed 16 cases of premenarchal ovarian torsion cases, it has been found that most of the cases had normal-size ovary (69.9%) 10.…”
Section: Discussionsupporting
confidence: 56%
“…Laparoscopy has been proven to be a safe approach for the treatment of AT in nonpregnant women [ 8 ]. Recent reports have indicated that conservative surgery, i.e., detorsion with or without cystectomy, does not increase thromboembolic complications and favors ovarian function preservation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adnexal torsion in premenarchal patients occurs rarely, its symptoms are similar to older patients, but involves a normal adnexa in 69% of cases [6]. Compared with older women, premenarchal patients with adnexal torsion are more commonly found with normal ovarian volume [1, 2, 7].…”
Section: Discussionmentioning
confidence: 99%